Inner Conflict and Moral Consciousness in Qamar al-Zamān: A Freudian Psychoanalytic Interpretation - Azzamsyah, Muhammad Raihan; Sa'adah, Rd. Siti (Muslim English Literature, 2025)
This study analyzes the dynamics of the personality structure of the characters in the tale " Qamar al-Zamān ibn al-Malik Shahramān” in Alf Laylah wa-Laylah using Sigmund Freud's psychoanalytic approach. In contrast to previous studies that focused on the protagonist, this study broadens the scope of analysis to four central figures: Qamar al-Zamān, Princess Budūr, King Shahramān, and Princess Ḥayāt al-Nufūs, to reveal the interrelation of psychic conflicts that build narratives. This research uses a qualitative descriptive method with hermeneutic textual analysis techniques. The research findings show that: (1) Qamar al-Zamān undergoes a transformation from an intellectual defense mechanism to a mature Ego integration; (2) Princess Budūr manifests a shift in instinctual energy from Thanatos (aggression) to Eros (obsessive love); and (3) King Shahramān represents the rigidity of the external Superego that triggers an existential crisis. The study concludes that narrative stability in classical literature is highly dependent on the achievement of psychological equilibrium of its characters. The story's conflict is proven to be not merely an external event, but an externalization of the failure of the Ego's mediation function in reconciling the Id's urges and the demands of reality.